MAKNA SIMBOL UPACARA PERNIKAHAN ADAT SUKU LEMBAK DAN RELEVANSINYA DENGAN NILAI-NILAI KEISLAMAN (STUDI TRADISI DI DESA KEMBANG SERI KECAMATAN TALANG EMPAT KABUPATEN BENGKULU TENGAH) - Ahmad Fikram Ahmad (Manthiq, 2017)
The  results  of the  study  explained,  Firstceremonial procession  namely:  consensus night,  the ceremony, the  bride  besanding, bridal  becampur, menyalang, and  keduri  disband the  committee. Both forms of symbolsKetan fry, Lenguai,4-5 rice dishes,  all existing side dishes,  umbrellas, fans, Sarafal Anam, seven  bars cigarette, cigarette case  (where cigarettes), limes letter (lemon), flowers, water,  a small basin, saffron  rice  portion,Chicken.Third In the  implementation wedding ceremony tribal Lembak  raised  many Islamic values  which  contain  values  of divinity, the value of deliberation, the value of mutual  help and  the value of moral education in life married to each  other along together, love one another and help each  other to live a married life.